MOTIVATION IN UNIVERSITY STUDENTS - Mas Tous, Carmen; Medinas Amorós, Magdalena (Anales de Psicología / Annals of Psychology, 2007)
Nowadays, Spanish universities hold a debate about how to adapt to the European Space for High Education. This process of adapta-tion involves a new concept in university education that implies reframing lecturer’s role and emphasizing students own learning capabilities. This study has its origin in some questions that arise in university teaching: What does motivate university students? What variables have an influence in their motivation? We believe the answers of these questions are the starting point in order to know what university lecturers can do to moti-vate students in the best way. Furthermore, this helps us find out what strategies can be used to enhance motivation and thus learning performance. Results pointed out the importance of fomenting intrinsic motiva-tion in this educational period and the relevance of the lecturer’s role in motivating student’s learning process. This clearly shows that faculty formation programs for university teachers are needed.